Agroforestry in the Indo-gangetic Plains: An Analysis - Pathak, P. S.; Pateria, H. M. (Indian Journal of Agroforestry, 2020)
Indo-gangetic plains, covering an area of 50.34 million hectare, are 15.31% of the total area of India where its 32.8% human and 35.18% of animal population lives. The alluvial plains are resource rich region in terms of environmental resources and support high production of its rice - wheat cropping system. Although agriculture is the main occupation, yet forestry and agroforestry development rate have been faster to support the requirements of timber, firewood, fodder, pulp and other requirements of the large population. The paper is an attempt to describe the region, its resources and factors that control the development and adoption of agroforestry in the region. It analyses the socio-economic mileue that limits its adoption and the needs for transfer of technology to augment it. It also attempts to propose the agroforestry interventions for the region.